Die Freizeittheologie mit besonderer Berücksichtigung der Ruhetheologie - Maciej Ostrowski (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
The author performs an analysis of „theological places” („loci theologici”), as the basis on which leisure theology can be developed. These are: time theology (a linear concept of time, which means that time is a gift to man, if properly used), freedom theology (freedom not as a discharge from obligations but as the possibility to do good), new creation theology (renewal made by the redemptive work of Christ), joy theology (joy of gifts of nature, community with other person, being granted God’s grace), feast theology (time given to a man in order that he could turn to supernatural matters). The author develops ‘rest theology’ extensively as one of the fundamental forms of spending free time. He searches for sources in numerous biblical texts, where this term has been used. Furthermore, he interprets, among others, how to understand God’s rest after he created the world, and how his repose becomes an example to follow for a human being. Moreover, the author explains what the final repose is to be for a person, and how man, living on earth, anticipates an eschatological rest.